Implementasi Konsep Asthabrata sebagai Landasan Hidup Generasi Z - Untoro, Haryo; Mustofa, Daffa Pharaja; Ulumudin, Miktahul (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
Generation Z is often referred to as the